The image of the Dar Al Harb female in selected texts of travel literature - قدّاح , رؤى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research is based on studying the image of the Dar al-Harb female In the travel texts, trying to show the extent to which the features of the anthropological discourse - which formulate the image of the other based on a previous communication discourse based on tribal provisions that regulate the traveler's vision of his other– appear in it by observing the female image in four travel texts, two of them are Eastern: The Journey of Ibn Fadhlan, and the first Journey of Abu Dolaf Al-Khazraji, and two Andalusian journeys: the Two Journeys of Al-Ghazal, and the Journey of Afuqai. The research reached some results: The most important of them are: the emergence of the features of the ethnographic discourse in all texts, and the four travelers revealing the position of the female body within the culture of the enemy, and displaying its heterosexualities based on explicit or implicit balances between it and the Muslim female ideal, and they used the female body as a means to expose The other and to expose the forms of societal corruption, relying in their value judgments on self-values ​​as universal values. The travelers alienated the negative attributes of heterogeneity related to the female body of the Dar al-Harb female, to create a state of aversion to her among Arab Muslim readers, to venerate self-values, and to triumph over the female Muslim ideal.